Meu game de educação financeira - Schimidt, Deilon Ricsom (2023)
This research is linked to the Graduate Program in Educational Technologies in Network of the Federal University of Santa Maria - PPGTER/ UFSM and seeks to propose a game for elementary school students, in order to assist in the teaching of Financial Education. For this, initially, a bibliographical research and a field research on the internet was made to become aware of the existence of possible on-line games linked to the theme and that are already used by young people, how these games present the construction of knowledge, how interactions occur between their participants and how the content is arranged. In order to bring Financial Education to the adolescent public of Elementary School through a methodology that stimulates research, knowledge sharing among students and interaction through teamwork, this game aims to identify the possibility of working the aforementioned content, which became part of the school curriculum from 2020 by the new BNCC, in a motivating and challenging way. It was carried out a survey of the theoretical conceptions about the Design Methodology, methodology which was based on this research and subsequently was provided, the game developed, to the group of students already mentioned for, through the opinion of adolescents, evaluate a possible restructuring of the game and the difficulties and facilities found in understanding the content. From this study it was possible to verify that the product developed, My Financial Education game, can be an alternative to diversify the way this content is presented in school, making the moments of study more attractive and enjoyable. You will need to redesign the product to make it more objective and accessible to other age groups.